Genome-wide analysis of genetic diversity in a germplasm collection including wild relatives and interspecific clones of garden asparagus - Sala, Tea; Puglisi, Damiano; Ferrari, Luisa; Salamone, Filippo; Tassone, Maria Rosaria; Rotino, Giuseppe Leonardo; Fricano, Agostino; Losa, Alessia (Frontiers in Plant Science, 2023)
Abstract The Asparagus genus includes about 240 species, the most important of which is garden asparagus (Asparagus officinalis L.) as it is a worldwide cultivated vegetable crop for its edible spear. Along with garden asparagus, other species are cultivated (e.g., Asparagus maritimus L.) or proposed as untapped sources of variability in breeding programs (e.g., Asparagus acutifolius L.). In the present work we applied reduced-representation sequencing to examine a panel of 378 diverse asparagus genotypes, including commercial hybrids, interspecific lines, wild relatives of garden asparagus, and doubled haploids currently used in breeding programs, which allowed the identification of more than 200K polymorphic SNPs. These SNPs were used to assess the extent of linkage disequilibrium in the diploid gene pool of asparagus and combined with preliminary phenotypic information to conduct genome-wide association studies for sex and traits tied to spear quality and production. Moreover, using the same phenotypic and genotypic information we fitted and cross-validated genome-enabled prediction models for the same set of traits. Overall, our analyses demonstrated that, unlike the diversity detected in wild species related to garden asparagus and in interspecific crosses, cultivated and wild genotypes of Asparagus officinalis L. show a narrow genetic basis which contributes to hampering the genetic improvement of this crop. Estimating the extent of linkage disequilibrium and providing the first example of genome-wide association study and genome enable prediction in this species, we concluded that, the asparagus panel examined in the present study can lay the foundation for dissecting the genetic bases of agronomically important traits and for implementing predictive breeding tools to sustain breeding.